2006
DOI: 10.1515/znc-2006-1-211
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal Activity and New Flavonoids from Egyptian Iris germanica L. (var. alba)

Abstract: The molluscicidal activity of leaf and rhizome extracts of Iris germanica L. (var. alba) against Biomphalaria alexandrina snails was evaluated and the rhizome extracts were found to be the most potent. Activity-guided fractionation revealed that the chloroform extract showed the highest molluscicidal activity (LC90 = 1.26 mg/l) among the tested extracts of the rhizomes. Fraction B prepared from the chloroform extract was the most potent molluscicide (LC90 = 0.96 mg/l) in addition, it showed a significant heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 0 publications
1
18
0
1
Order By: Relevance
“…This result is similar to that of Mohamed et al [ 42 ] who reported the cercariacidal activity of the crushed seed of Nigella sativa to be both time and concentration dependent. This finding is also in line with the reported data for Milletia thoningii by Perret et al [ 43 ] and Irish germanica by Singaba et al [ 23 ] who reported the time-concentration relationship of the plants extracts . Other studies by Rug and Rupel [ 15 ] using different solvent extracts of Jatropha curcas and by Ahmed and Ramzy [ 44 ] using aqueous extract of Solanum nigrum also reported similar findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is similar to that of Mohamed et al [ 42 ] who reported the cercariacidal activity of the crushed seed of Nigella sativa to be both time and concentration dependent. This finding is also in line with the reported data for Milletia thoningii by Perret et al [ 43 ] and Irish germanica by Singaba et al [ 23 ] who reported the time-concentration relationship of the plants extracts . Other studies by Rug and Rupel [ 15 ] using different solvent extracts of Jatropha curcas and by Ahmed and Ramzy [ 44 ] using aqueous extract of Solanum nigrum also reported similar findings.…”
Section: Discussionsupporting
confidence: 92%
“…In both cases, the series of concentrations were prepared in a final volume of 250 ml aged water. These concentrations were prepared by taking the calculated volume from the stock solution and then diluted with aged water until1000 ml [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The tested algae were thoroughly washed by sea water to remove extraneous matters, then dried in shade and finely grounded. Aqueous and ethanol extracts of the four different species of marine algae were prepared according the procedure of Singaba et al (2006). Identification of the algal species was carried out according to methods described by Chaumont (1993) and Barsanti and Gualtieri (2014) and was also checked by Dr. Manal El-Naggar, Professor of Microbiology and Head of Microbiology Department; National Institute of Oceanography and Fisheries, Alexandria, Egypt.…”
Section: Tested Algaementioning
confidence: 99%
“…Yield, 45%; m.p. 228e230 C; 1 3.9. 6-(Benzofuran-2-yl)-4-(3-(benzofuran-2-yl)-1-phenyl-1H-pyrazol-4-yl)-5,6-dihydropyrimidine-2(1H)-thione (14) To a solution of 3 (10 mmol) and thiourea (30 mmol) in ethanol (20 mL), ethanolic KOH (20 mmol, 5 mL) was added.…”
Section: -(Benzofuran-2-yl)-2-((3-(benzofuran-2-yl)-1-phenyl-1h-pyramentioning
confidence: 99%
“…This disease affects more than 200 million people and places with more than 600 million inhabitants are at risk of infection in more than 70 countries in the tropics WHO [1]. In view of its prevalence and morbidity this disease is a serious public health problem in many countries especially Egypt and one of the great efforts made to combat this disease is combating the water snails Biomphlaria alexandrina, the intermediate host of the infective phase of schistosoma mansoni, through molluscicides to control the vector snails with easy and cheap procedures.…”
Section: Introductionmentioning
confidence: 99%